Determination of Factors Affecting Individual Investor Behaviours: A Study on Bankers - İslamoğlu, Mehmet and Apan, Mehmet and Ayvalı, Adem (International Journal of Economics and Financial Issues, 2015)
In this study, it was aimed to investigate the factors that influence individual investor behaviour. The data used in the study were obtained via survey method from bankers in Bartın, Turkey. Descriptive analysis was conducted in order to summarize the empirical analysis results with numerical representation and factor analysis was done to measure the validity and reliability of the designed survey. Furthermore, the analysis regarding hypothesis tests was implemented by means of AMOS. As a result of the study, it was identified that 6 factors influenced individual investor behaviour. It was found that the highest correlation was between “Deliberate Investor Behaviour” and “Banking and Payment Behaviour”. Also, it was confirmed that 11 of the research hypotheses were accepted and that 4 of the research hypotheses were refused. Within this framework, it was concluded that there was a statistically significant relationship between the factors affecting individual investors’ investment behaviours. Keywords: Investment; Individual Investor Behaviour; Investment Tools; Socio-Economic Structure JEL Classifications: G02; G11; G20